2020
DOI: 10.1097/gme.0000000000001657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex hormones on coronavirus disease 2019: an analysis of 5,061 laboratory-confirmed cases in South Korea

Abstract: Objective: To evaluate the effect of female sex hormones on the clinical outcomes of coronavirus disease 2019 patients using national claims data. Methods: This retrospective cohort study used the Health Insurance Review and Assessment data of 5,061 adult patients with laboratory-confirmed coronavirus disease 2019 in South Korea from January 20 to April 8, 2020. To evaluate the effect of hormone therapy on clinical outcomes among women, subgroup analyses using age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…A study investigating 152,637 female users of a COVID Symptom Tracker Application in the UK reported that postmenopausal women had a higher rate of predicted COVID while pre-menopausal women taking the contraceptive pill had a significantly lower rate of predicted COVID-19 and hospitalizations with respect to their post-menopausal counterparts [17] . The authors of a study carried out in South Korea did not find any association between females who had been taking HT over the past year and morbidity and clinical outcomes of COVID-19 [19] . Although it is impossible to exclude that postmenopausal females are more susceptible to SARS-COV-2 infection due to age-related factors and comorbidities rather than to lower oestrogen levels, our data suggest that HT may play a protective role against COVID-19 in older females.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study investigating 152,637 female users of a COVID Symptom Tracker Application in the UK reported that postmenopausal women had a higher rate of predicted COVID while pre-menopausal women taking the contraceptive pill had a significantly lower rate of predicted COVID-19 and hospitalizations with respect to their post-menopausal counterparts [17] . The authors of a study carried out in South Korea did not find any association between females who had been taking HT over the past year and morbidity and clinical outcomes of COVID-19 [19] . Although it is impossible to exclude that postmenopausal females are more susceptible to SARS-COV-2 infection due to age-related factors and comorbidities rather than to lower oestrogen levels, our data suggest that HT may play a protective role against COVID-19 in older females.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, androgens may predispose males to a more severe COVID-19 progression [16] . To the best of our knowledge, only a few studies have investigated the sex- and gender differences linked to the SARS-CoV-2 infection [ 2 , 3 , 5 ] and the potential therapeutic role of sex hormones [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…13 Lee et al, did not find a positive correlation between menopause with severe disease. 14 On the other hand, Neha et al, 12 found a statistically significant difference in oxygen demand, hospital stay, and progression to severe illness in the menopause group compared to the non-menopause group. Our analysis also observed similar conclusions that the Covid-19 is more severe among postmenopausal women.…”
Section: Discussionmentioning
confidence: 96%
“…failed to show any beneficial effect of menopausal hormone therapy (MHT) on COVID-19 postmenopausal women. [ 29 ] Similarly, Bonaccorsi et al . could not find any evidence that women on MHT have a lower risk than untreated women.…”
Section: Discussionmentioning
confidence: 99%